IMPLEMENTATION OF COOPERATIVE DIGITALIZATION AT KUTA MIMBA COOPERATIVE IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Surya Dewi Rustariyuni; Ni Kadek Eka jayanthi; AAIN Marhaeni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The writing of this paper aims to determine the paradigm of sustainable development of cooperative digitalization in the era of the Industrial Revolution 4.0 in order to increase competitiveness. This paper employs a literature review method (library research). From the discussion, it can be concluded that the decline in the number of cooperatives over the past five years has not diminished the intention of other cooperative actors to continue innovating and enhancing their creativity. One of the cooperatives implementing digitalization in the era of the Industrial Revolution 4.0 is the Kuta Mimba Cooperative, with digital services at hand that can be accessed anywhere and at any time. The government provides training assistance for other cooperatives to implement digital services. Thus, the three economic pillars, one of which is cooperatives, develop on an equal footing with state-owned enterprises and the private sector. Cooperative digitalization in the era of the Industrial Revolution 4.0 currently requires the contribution of ideas from the millennial generation to ensure the sustainability of cooperatives in the future.